Community Participation in Public Schools : The Impact of Information Campaigns in Three Indian States - Pandey, Priyanka; Goyal, Sangeeta; Sundararaman, Venkatesh (World Bank, Washington, DC, 2012)
This study evaluates the impact of a community-based information campaign on school performance from a cluster randomized control trial. The campaign consisted of eight to nine public meetings in each of 340 treatment villages across three Indian states to disseminate information to the community about its state mandated roles and responsibilities in school management. The findings from the first follow-up 2-4 months after the campaign show that providing information through a structured campaign to communities had a positive impact in all three states. In two states there was a significant and positive impact on reading (14-27 percent) in one of the three grades tested; in the third state there was a significant impact on writing in one grade (15 percent) and on mathematics in the other grade tested (27 percent). The intervention is associated with improvement in teacher effort in two states. Some improvements occurred in the delivery of certain benefits entitled to students (stipend, uniform, and mid day meal) and in process variables such as community participation in each of the three states. Follow-up research needs to examine whether there is a systematic increase in learning when the impact is measured over a longer time period and whether a campaign sustained over a longer time is able to generate greater impact on school outcomes.